2011
DOI: 10.1007/s10482-011-9602-1
|View full text |Cite|
|
Sign up to set email alerts
|

Bacteria associated with the pinewood nematode Bursaphelenchus xylophilus collected in Portugal

Abstract: In this study, we report on the bacterial community associated with the pinewood nematode Bursaphelenchus xylophilus from symptomatic pine wilted trees, as well as from long-term preserved B. xylophilus laboratory collection specimens, emphasizing the close bacteria-nematode associations that may contribute to pine wilt disease development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 18 publications
3
45
0
Order By: Relevance
“…A total of 98 sequences were found: 60 from Portugal in 2010 [8]; 21 from Portugal in 2011 [26]; 2 from China in 2012 [29] and 15 from China in 2013 [12]. The sequences were aligned and the dendrograms were constructed as mentioned above.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 98 sequences were found: 60 from Portugal in 2010 [8]; 21 from Portugal in 2011 [26]; 2 from China in 2012 [29] and 15 from China in 2013 [12]. The sequences were aligned and the dendrograms were constructed as mentioned above.…”
Section: Methodsmentioning
confidence: 99%
“…In Republic of Korea, the bacterial genus associated to PWN found in common with China was Serratia [25]. Recently, it was shown that in Portugal bacteria associated with PWN were mainly belonging to the genera Pseudomonas , Burkholderia , and to the family Enterobacteriaceae [8], [26]. Others suggested that bacteria, carried by the PWN, are phytotoxin producers and interact with the nematode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As complex mixtures, EOs may display several biological activities which makes them desirable biopesticides, being able to control not just the targeted pest but also opportunistic species and resistant strains. This is of particular interest in phytoparasitic nematode control since complex disease symptoms are also commonly associated with accompanying pathogenic microbiota (Back et al, 2002;Vicente et al, 2011). Several EOs, such as those of Cinnamomum zeylanicum (Kong et al, 2006); Boswellia carterii, Paeonia moutan, Perilla frutescens, Schizonepeta tenuifolia (Choi et al, 2007a); Thymus vulgaris (Kong et al, 2007); Litsea cubeba, Pimenta dioica, Trachyspermum ammi ; Coriandrum sativum and Liquidambar orientalis (Kim et al, 2008) have revealed strong activities against B. xylophilus.…”
Section: Introductionmentioning
confidence: 99%
“…In Korea, the genera Burkholderia, Brevibacterium, Ewingella, Enterobacter and Serratia appear to be associated with the PWN (Kwon et al 2010). More recently, in Portugal, the genera Burkholderia and Pseudomonas, as well as other bacteria from the Enterobacteriaceae family, were found to be associated with B. xylophilus (Proença et al 2010;Vicente et al 2011). However, other studies have shown that the PWN is able to cause pathogenicity under aseptic conditions (Tamura 1983;Kuroda and Ito 1992).…”
mentioning
confidence: 99%